Needs Analysis for Smart Box Media Development in Energy Transformation Instruction: Enhancing Critical Thinking Skills of Fourth-Grade Elementary Students - Ma’rufah, Ulil; Suratmi, Suratmi; Susiloningsih, Esti (Journal of Innovation and Research in Primary Education, 2025)
Elementary students face significant challenges comprehending abstract energy transformation concepts, requiring innovative instructional media to bridge gaps between theoretical knowledge and concrete understanding while developing critical thinking skills. This descriptive quantitative study analyzed needs of 63 fourth-grade students and two teachers from SDN 5 Mangsang and SDN 6 Mangsang through structured questionnaires assessing six dimensions: pedagogical, technical, cognitive, aesthetic, sociocultural, and evaluative aspects. Data were analyzed using percentage frequencies with established categorical criteria. Findings revealed evaluative features (100%), aesthetic design (96.81%), and sociocultural relevance (95.34%) as highest priority dimensions, followed by cognitive support (86.24%) and pedagogical engagement (77.18%), while technical accessibility (51.75%) required particular attention. Teachers demonstrated unanimous agreement (100%) across all dimensions, emphasizing training needs, infrastructural readiness, and media's potential to enhance critical thinking. Students exhibited strong preference for interactive, visually appealing media with immediate feedback mechanisms, despite demonstrating low baseline comprehension of energy transformation concepts. Results validate multimodal representation frameworks and situated learning theories while documenting specific stakeholder requirements for Smart Box media development. The study establishes empirical foundation for evidence-based instructional media design that integrates assessment capabilities, visual appeal, cultural responsiveness, conceptual scaffolding, and practical accessibility to address documented deficiencies in conventional elementary science instruction.